The prudential toolkit with shadow banking - Kinda Hachem; Martin Kunci (Federal Reserve Bank of New York, 2025)
Several countries now require banks or money market funds to impose state-contingent costs on shortterm creditors to absorb financial stress. We study these requirements as part of the broader prudential toolkit in a model with five key ingredients: banks may face an aggregate stress state with high withdrawals; a fire-sale externality motivates a mix of non-contingent and state-contingent regulation; banks may use shadow technologies to circumvent regulation; parameters of the shadow technologies may be private information; and bailouts may occur. We characterize the optimal policy for various combinations of these ingredients and demonstrate that the threat of shadow activities constrains statecontingent regulation more than noncontingent regulation, especially when imperfect information and limited commitment coexist. The planner triggers shadow activities with positive probability under imperfect information, and shadow activities that deplete resources in the stress state elicit larger bailouts under limited commitment, rendering the requirement of state-contingent costs a weak instrument.
Keywords: D62; E61; G01; G21; G28; 330; pecuniary externality; bailout; bail-in; shadow banking; optimal regulation